Utilization of Tofu Dregs Flour in Making Snack Bars for People with Diabetes Mellitus - Ni Putu Diah Cahyani Subamia; Komang Ayu Nocianitri; I Dewa Gede Mayun Permana (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2020)
Type II diabetes mellitus due to an unhealthy lifestyle, one of which is the lack of fiber in daily food consumption. One food that has a high fiber content is tofu dregs. The purpose of this study was to determine substitution of wheat flour with tofu dregs flour to produce a snack bar with the best characteristics, and determine the effect of consumption of snack bar from tofu dregs on blood sugar content in rats. The research was conducted two steps. Step I: Formulation of snack bar using a completely randomized design with tofu dregs flour concentration of 0 %, 10 %, 20 %, 30 %, 40 %, and 50 %. The variables of this study were the content of water, ash, protein, fat, carbohydrates, sensory tests, and effectiveness tests. Step II: the best characteristic snack bar in the step I was used experimental rats. This step used true experimental design with pre-post test control group design. The variables of study were blood glucose levels before treatment and after treatment. The treatment group consisted of normal, negative, positive control, and snack bar. The results of the first step of the research showed that substitution of wheat flour with 40 % tofu dregs produced the best characteristic snack bar with 17.19 % water content, 1.33 % ash content, 11.03 % protein, 20.53 % fat, 49.92 % carbohydrate, light brown color, unpleasant aroma, distinctive soy taste, crumb texture, 0.63 % water soluble food fiber, 1.57 % water insoluble fiber, and total food fiber 2.36 %. The results of the second step of the study showed that the provision of substitution of wheat flour with tofu dregs flour 40 % could reduce blood sugar levels in diabetic mellitus rats until normal, start 290 mg/dl to 108.5 mg/dl. Tofu dregs flour can be used for snack bar formulations for people with diabetes mellitus.